ANALYSIS OF SHARIA ECONOMIC LAW ON PALM OIL SELLING PRACTICES - Yuniartik Yuniartik (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This research is motivated by various fraud issues in the implementation of buying and selling palm oil in Sijang Village, Galing District . This fraud, the middlemen carried out price cuts and weighing unilaterally which can harm farmers. This research is included in field research with descriptive qualitative approach . The research location is located in Sijang Village, Galing District, Sambas Regency . The subjects in this study were farmers , buyers (middlemen) , harvesters and weighers in Sijang Village, Galing District . Researchers use 3 methods in data collection namely observation, interviews and documentation. Results This research shows that the buying and selling of palm oil in Sijang Village, Galing District , has not fulfilled the conditions set by sharia economic law . Buying and selling of palm oil implemented in Sijang Village can provide a very large opportunity for someone to do fraud. Buying and selling palm oil with a unilateral price cut and weighing system is not meet the legal terms of consent and qabul where someone who transacts must be in the same place or be in a different place but at the same time and know each other. According to the analysis of Economic Law Sharia lawful buying and selling must fulfill the pillars and conditions that have been determined, while the sale and purchase of palm oil with price cuts and unilateral weighing in Sijang Village has not met the legal requirements determined by Islamic law.